Al-Qur’an dan Kebenaran Ilmiah: Telaah Epistemologis atas Relasi Wahyu dan Sains - Rahmatul Qadri; Ummul Inayah; Ramsiah Tasruddin (Advances In Education Journal, 2025)
Scientific truth is frequently treated as the primary framework for explaining reality, encouraging scientism and marginalizing non-empirical knowledge. This article examines the epistemological relationship between the Qur’an and scientific truth, with a critical focus on the discourse of i‘jāz ‘ilmī. A qualitative library-based method is employed through systematic analysis of contemporary scholarly works on the philosophy of science, Qur’anic epistemology, and science–religion relations. The study finds that the Qur’an and scientific knowledge operate within distinct but interconnected epistemological domains. Scientific truth is provisional and context-dependent, whereas Qur’anic discourse provides ethical orientation and reflective meaning rather than empirical explanation. The findings demonstrate that attempts to verify Qur’anic truth through science risk epistemological reductionism. The article proposes a non-reductive framework that positions Qur’anic cosmological verses as reflective signs encouraging intellectual inquiry and moral responsibility, thereby strengthening constructive dialogue between revelation and science.